Growth and structural change in Indian Economic - Preeti Devi (Innovative Research Thoughts, 2023)
This chapter examines growth and structural change in the Indian economy since independence, focusing on the key drivers and critical junctures that led to changes in economic policies and their consequences for growth and distribution. It then analyzes three central puzzles of Indian economic development: 1) Why, despite a persistent policy and intellectual concern with poverty, has India’s record on this score been modest, especially with regard to human capital indicators? 2) Why has India managed reasonably sound macroeconomic policies, in sharp contrast to its innumerable microeconomic inefficiencies? and 3) What explains India’s modest growth in the early decades after independence, under good governance, but much more rapid rates of growth in recent decades—second only to China among large economies—even as corruption has mushroomed? The paper concludes with some observations on the Indian State and argues that the foremost challenge that India faces is strengthening public institutions and governance.